Agriculture collectives in North Bengal - International Water Management Institute (2022)
In South Asia, over 80% of farmers cultivate two hectares or less. Most farms are technically constrained and economically non-viable. As a novel experiment, between 2015-2019 a set of farmer collectives were piloted by a consortium of NGO and research partners in the Eastern Gangetic Plains, to see if this could help marginal and small farmers overcome their constraints in a region with exploitative landlord-tenant relations and poor irrigation access. This participatory action research project entailed the formation of collectives of 4-10 farmers (of varying gender composition), each cultivating contiguous plots and collaborating in land management, production and marketing in varying degrees. The project provided irrigation through electric and solar boreholes but twinning this with a collective approach to create a large contiguous plot was critical to make the irrigation practical and efficient. This approach enabled resource-poor farmers to farm all year round. All the groups reported higher crop yields, and tenant farmers gained more bargaining power with landlords. This documentary focuses on the West Bengal collectives. It probes the benefits the farmers have reaped as well as the challenges they continue to face in terms of labour sharing and marketing, especially under the twin shadows of the pandemic and climate change. The collectives were implemented by the Centre for the Development of Human Initiatives (CDHI), with support from the University of Southern Queensland, the International Water Management Institute (IWMI), the University of Birmingham and North Bengal Agricultural University (UBKV). Sugden, Agarwal, Leder, Saikia, Kumar, Ray (2020). Experiments in farmers’ collectives in Eastern India and Nepal. Journal of Agrarian Change. http://dx.doi.org/10.1111/joac.12369